Hormonal Changes in Menopause and Orexin-A Action - Giovanni Messina; Andrea Viggiano; Vincenzo De Luca; Antonietta Messina; Sergio Chieffi; Marcellino Monda (Obstetrics and Gynecology International)
Menopause is a period of significant physiological changes that may be associated with increased body weight and obesity-related diseases. Many researches were conducted to assess the contribution of factors such as estrogen depletion, REE decline, and aging to weight gain. An increase in orexin-A plasma levels, paralleling lower estrogen levels, was found during menopause. Orexins are hypothalamic neuropeptides recently discovered, involved in the regulation of feeding behaviour, sleep-wakefulness rhythm, and neuroendocrine homeostasis. Orexins might offer the missing link between postmenopausal hypoestrogenism and other manifestations of the menopausal syndrome, including appetite and weight changes and increase in cardiovascular risk.